NY-ESO-1 Based Immunotherapy of Cancer: Current Perspectives - Thomas, Remy; Al-Khadairi, Ghaneya; Roelands, Jessica; Hendrickx, Wouter; Dermime, Said; Bedognetti, Davide; Decock, Julie (Frontiers in Immunology, 2018)
NY-ESO-1 or New York esophageal squamous cell carcinoma 1 is a well-known cancer testis antigen with re-expression in numerous cancer types. Its ability to elicit spontaneous humoral and cellular immune responses, together with its restricted expression pattern, have rendered it a good candidate target for cancer immunotherapy. In this review, we provide background information on NY-ESO-1 expression and function in normal and cancerous tissues. Furthermore, NY-ESO-1 specific immune responses have been observed in various cancer types, however their utility as biomarkers are not well determined. Finally, we describe the immune-based therapeutic options targeting NY-ESO-1 that are currently in clinical trial. We will highlight the recent advancements made in NY-ESO-1 cancer vaccines, adoptive T cell therapy and combinatorial treatment with checkpoint inhibitors; and will discuss the current trends for future NY-ESO-1 based immunotherapy.